The capsid lattice engages a bipartite NUP153 motif to mediate nuclear entry of HIV-1 cores - Shen, Qi; Kumari, Sushila; Xu, Chaoyi; Jang, Sooin; Shi, Jiong; Burdick, Ryan C.; Levintov, Lev; Xiong, Qiancheng; Wu, Chunxiang; Devarkar, Swapnil C.; Tian, Taoran; Tripler, Therese N.; et al. (Proceedings of the National Academy of Sciences, 2023)
Increasing evidence has suggested that the HIV-1 capsid enters the nucleus in a largely assembled, intact form. However, not much is known about how the cone-shaped capsid interacts with the nucleoporins (NUPs) in the nuclear pore for crossing the nuclear pore complex. Here, we elucidate how NUP153 binds HIV-1 capsid by engaging the assembled capsid protein (CA) lattice. A bipartite motif containing both canonical and noncanonical interaction modules was identified at the C-terminal tail region of NUP153. The canonical cargo-targeting phenylalanine-glycine (FG) motif engaged the CA hexamer. By contrast, a previously unidentified triple-arginine (RRR) motif in NUP153 targeted HIV-1 capsid at the CA tri-hexamer interface in the capsid. HIV-1 infection studies indicated that both FG- and RRR-motifs were important for the nuclear import of HIV-1 cores. Moreover, the presence of NUP153 stabilized tubular CA assemblies in vitro. Our results provide molecular-level mechanistic evidence that NUP153 contributes to the entry of the intact capsid into the nucleus.